Quantifying discoloration caused by the indoor fungus Penicillium rubens on building material at controlled humidity. (August 2015) - Bekker, M.; Erich, S.J.F.; Hermanns, S.P.M.; van Maris, M.P.F.H.L.; Huinink, H.P.; Adan, O.C.G.
Abstract: Fungal growth in the indoor environment can affect human health by causing allergic reactions and respiratory symptoms. In the search for a solution to prevent or limit fungal growth in the indoor environment it is important to know how parameters such as temperature, substrate, and humidity affect fungal growth. Up to now, no general accepted method is applied to measure surface discoloration due to fungal growth on building and finishing materials. Reproducibility of measurements is difficult due to the non-transparent nature of most finishing materials, furthermore is fungal growth on porous materials relative slow and sparse. The aim of this paper is to present a novel method to accurately measure fungal growth, resulting in discoloration of a porous building material (gypsum), as a function of time under controlled temperature and humidity conditions. To this end, the "Fungal Observatory Climate controlled aUtomized Set-up" (FOCUS) was developed. The surface discoloration of gypsum, caused by sporulation of Penicillium rubens (formerly Penicillium chrysogenum ), was quantified using digital imaging over time. The pixel value intensities of acquired images were used to determine a measure of discoloration of the surface, and discoloration of the gypsum surface was plotted in a curve. In parallel, gypsum samples were studied with environmental scanning electron microscopy to relate discoloration (or its absence) with the developmental stage of the fungus. The method described in this paper is unsuitable to determine fungal growth on site, however the method is suitable to assess fungal growth under controlled conditions on finishing materials. Highlights: A novel method to measure fungal growth on building materials. Growth on gypsum quantified by image analysis. Temperature and humidity conditions accurately controlled.